2014
DOI: 10.1001/jamaoto.2014.1990
|View full text |Cite
|
Sign up to set email alerts
|

Stroke After Adenotonsillectomy in Patients With Undiagnosed Moyamoya Syndrome

Abstract: Clinicians should be aware of an elevated prevalence of moyamoya syndrome in Down syndrome and sickle cell disease populations and should consider moyamoya syndrome in the differential diagnosis of postoperative stroke. Stroke risk is magnified in the perioperative setting related to perioperative dehydration and hypotension. Awareness and screening for cerebral vasculopathy in high-risk populations could prompt measures to decrease the occurrence of postoperative strokes after adenotonsillectomies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…No reports of Ap/twig-like MCA causing cerebral infarction associated with extracranial surgery could be found within the scope of the investigation. However, it has been reported that moyamoya disease, which also exhibits dysplasia of the middle cerebral artery, causes cerebral infarction after extracranial surgery [ 10 ]. In addition, since the localization of cerebral infarction occurred only in a limited area of the MCA region, it is highly possible that Ap/twig-like MCA was the cause of the cerebral infarction in this case.…”
Section: Discussionmentioning
confidence: 99%
“…No reports of Ap/twig-like MCA causing cerebral infarction associated with extracranial surgery could be found within the scope of the investigation. However, it has been reported that moyamoya disease, which also exhibits dysplasia of the middle cerebral artery, causes cerebral infarction after extracranial surgery [ 10 ]. In addition, since the localization of cerebral infarction occurred only in a limited area of the MCA region, it is highly possible that Ap/twig-like MCA was the cause of the cerebral infarction in this case.…”
Section: Discussionmentioning
confidence: 99%
“…Acute neurological symptoms and signs are common in SCD and, as well as stroke, include transient ischaemic attack (TIA) [ 8 ], headaches [ 9 , 10 ], seizures [ 8 , 11 , 12 ] and coma [ 13 ]. Altered mental status with or without reduced level of consciousness, headache, seizures, visual loss or focal signs can occur in numerous contexts, including infection [ 14 ], acute chest syndrome (ACS) [ 15 ], acute anaemia [ 16 ], after surgery [ 17 ], transfusion [ 18 ] or immunosuppression [ 19 ] and apparently spontaneously [ 6 ]. For example, in one large series of patients with SCD and ACS, 3% of patients had neurological symptoms at presentation, and these symptoms developed in a further 7–10% as a complication of ACS [ 20 ].…”
Section: Introductionmentioning
confidence: 99%